Capital markets union in Europe - Busch, Danny; Avgouleas, Emilios; Ferrarini, Guido (Oxford : Oxford University Press, 2018)
'Capital Markets Union in Europe' analyses the legal and economic aspects of the plans for a Capital Markets Union (CMU) in Europe, which will have a major impact on financial markets and institutions both in the region and beyond.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 8, 2018).
Keywords: Capital market -- European Union countries; Finance and Accounting; Economics